2021
DOI: 10.1085/jgp.202012860
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of sarcomeric movement regulates left ventricular pump function in the in vivo beating mouse heart

Abstract: Sarcomeric contraction in cardiomyocytes serves as the basis for the heart’s pump functions. It has generally been considered that in cardiac muscle as well as in skeletal muscle, sarcomeres equally contribute to myofibrillar dynamics in myocytes at varying loads by producing similar levels of active and passive force. In the present study, we expressed α-actinin–AcGFP in Z-disks to analyze dynamic behaviors of sequentially connected individual sarcomeres along a myofibril in a left ventricular (LV) myocyte of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 62 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…Nanometer-scale changes in the length of a single sarcomere result in a large change in the contractile response ( Fukuda et al, 2001 ; Serizawa et al, 2011 ; Kobirumaki-Shimozawa et al, 2014 ; Rassier 2017 ). At present, the intracellular inhomogeneity in SL has been shown for isolated skinned and intact cardiomyocytes as well as in the in-vivo mouse heart ( Sarai et al, 2002 ; Herzog et al, 2010 ; Serizawa et al, 2011 ; Shintani et al, 2014 ; Kobirumaki-Shimozawa et al, 2016 ; Shimozawa et al, 2016 ; Kobirumaki-Shimozawa et al, 2021 ). This inhomogeneity increases upon the activation of the skeletal and cardiac myofibril ( Telley et al, 2006a ; Shimamoto et al, 2009 ; Moo et al, 2017 ; Rassier, 2017 ; Moo and Herzog, 2018 ) or upon an increase in intracellular Ca 2+ content ( Sarai et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanometer-scale changes in the length of a single sarcomere result in a large change in the contractile response ( Fukuda et al, 2001 ; Serizawa et al, 2011 ; Kobirumaki-Shimozawa et al, 2014 ; Rassier 2017 ). At present, the intracellular inhomogeneity in SL has been shown for isolated skinned and intact cardiomyocytes as well as in the in-vivo mouse heart ( Sarai et al, 2002 ; Herzog et al, 2010 ; Serizawa et al, 2011 ; Shintani et al, 2014 ; Kobirumaki-Shimozawa et al, 2016 ; Shimozawa et al, 2016 ; Kobirumaki-Shimozawa et al, 2021 ). This inhomogeneity increases upon the activation of the skeletal and cardiac myofibril ( Telley et al, 2006a ; Shimamoto et al, 2009 ; Moo et al, 2017 ; Rassier, 2017 ; Moo and Herzog, 2018 ) or upon an increase in intracellular Ca 2+ content ( Sarai et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…end-diastole and end-systole). Highly precise evaluation of SL variability can be achieved using Z-disk specific fluorescent labeling, which has been implemented in skinned and cultured cardiomyocytes ( Serizawa et al, 2011 ; Shintani et al, 2014 ; Kolb et al, 2016 ) and recently in living mice in vivo ( Kobirumaki-Shimozawa et al, 2016 ; Kobirumaki-Shimozawa et al, 2018 ; Kobirumaki-Shimozawa et al, 2021 ). It should be noted that, the SL range obtained in our study was found to be similar to that obtained by Z-disk labeling and reported in ( Kobirumaki-Shimozawa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations